2014
DOI: 10.1371/journal.pone.0092495
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Dengue Virus Infection in Mice by Administration of Antibodies against Modified Nonstructural Protein 1

Abstract: BackgroundInfection with dengue virus (DENV) may cause life-threatening disease with thrombocytopenia and vascular leakage which are related to dysfunction of platelets and endothelial cells. We previously showed that antibodies (Abs) against DENV nonstructural protein 1 (NS1) cross-react with human platelets and endothelial cells, leading to functional disturbances. Based on sequence homology analysis, the C-terminal region of DENV NS1 protein contains cross-reactive epitopes. For safety in vaccine developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 56 publications
(70 reference statements)
4
74
0
1
Order By: Relevance
“…Abs against C-terminal residues of NS1 have been shown to cross-react with platelets and endothelial cells during dengue infection. Deletion of the C-terminal region 271-352 of NS1 abolished anti-NS1-mediated platelet dysfunction, endothelial damage, and bleeding tendency (37,38). Our results further demonstrated that Abs against C-terminal NS1 may also cause abnormal Plg activation.…”
Section: Discussionsupporting
confidence: 67%
“…Abs against C-terminal residues of NS1 have been shown to cross-react with platelets and endothelial cells during dengue infection. Deletion of the C-terminal region 271-352 of NS1 abolished anti-NS1-mediated platelet dysfunction, endothelial damage, and bleeding tendency (37,38). Our results further demonstrated that Abs against C-terminal NS1 may also cause abnormal Plg activation.…”
Section: Discussionsupporting
confidence: 67%
“…29 As increased bleeding time is an important indicator of DENV pathogenesis, we inoculated WT and Kit W-sh/W-sh mice with 1 9 10 9 PFU/mouse of DENV and determined the bleeding time on 2 and 3 days p.i. The results showed that DENV infection caused prolonged bleeding time, both in WT and Kit W-sh/W-sh mice.…”
Section: Bleeding Times Of Denv-infected Wt and Kitmentioning
confidence: 99%
“…Now we could say that it is quite possible that development of PAIgM is contributing to the increasing vascular permeability. Krishnamurti et al demonstrated the platelets binding to the endothelial cells that were infected with dengue-virus [27,28] . As vascular permeability increases with DHF, so for this mechanism active platelets that are associated with denguevirus, anti-dengue virus IgM and endothelial cells that are infected with dengue-virus may be important [9,17,29] .…”
Section: Discussionmentioning
confidence: 99%